2020
DOI: 10.1044/2019_lshss-19-00011
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Development of a Home Review Program to Promote Preschoolers' Vocabulary Skills: Social Validity and Learning Outcomes

Abstract: Purpose This article describes the iterative development of a home review program designed to augment vocabulary instruction for young children (ages 4 and 5 years) occurring at school through the use of a home review component. Method A pilot study followed by two experiments used adapted alternating treatment designs to compare the learning of academic words taught at school to words taught at school and reviewed at home. At school, chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 66 publications
4
18
0
Order By: Relevance
“…Vocabulary learning strategies refer to "a wide spectrum of strategies used as part of an on-going process of vocabulary learning" (Gu and Johnson, 1996, p. 669). In line with O' Malley and Chamot's (1990) classifications of LLSs, Gu and Johnson (1996) developed an elaborate list of metacognitive and cognitive strategies that may be used from initial contact with words to putting them to use, which include categorizations such as selective attention, self-initiation, guessing, dictionary use, note-taking, memorization strategies, and activation. Schmitt (1997) and Fan (2003) have also constructed VLS questionnaires, based on O' Malley and Chamot's (1990) and Oxford's (1990) frameworks.…”
Section: Literature Review Vlss and Related Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Vocabulary learning strategies refer to "a wide spectrum of strategies used as part of an on-going process of vocabulary learning" (Gu and Johnson, 1996, p. 669). In line with O' Malley and Chamot's (1990) classifications of LLSs, Gu and Johnson (1996) developed an elaborate list of metacognitive and cognitive strategies that may be used from initial contact with words to putting them to use, which include categorizations such as selective attention, self-initiation, guessing, dictionary use, note-taking, memorization strategies, and activation. Schmitt (1997) and Fan (2003) have also constructed VLS questionnaires, based on O' Malley and Chamot's (1990) and Oxford's (1990) frameworks.…”
Section: Literature Review Vlss and Related Researchmentioning
confidence: 99%
“…Studies on use of VLSs (Gu and Johnson, 1996;Lawson and Hogben, 1998;Fan, 2003;Gu, 2003) have found that successful learners used a wider variety of VLSs in an orchestrated manner, with their own characteristics. Studies have also found that individual differences and learning contexts can exert influence on the choice and use of VLSs.…”
Section: Literature Review Vlss and Related Researchmentioning
confidence: 99%
See 3 more Smart Citations